Strategi Inovatif Pembelajaran Mendalam: Upaya Meningkatkan Kompetensi Guru Sekolah Dasar - Nurhidayati, Nurhidayati; Tusino Tusino; Rida Desty Ariyanti (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Deep learning is a learning approach that emphasizes in-depth understanding of concepts and the development of critical, creative, collaborative, and communicative thinking skills. Although this approach aligns with the demands of a competency-based curriculum, its implementation at the elementary school level still faces various challenges. Based on a preliminary survey, 65% of elementary school teachers in partner schools admitted to experiencing difficulties in implementing deep learning effectively in the classroom. This study aims to identify innovative strategies that can improve teacher competency through a structured training program. The training activities involved 120 teachers from 10 elementary schools who are members of the teacher working group (KKG), with a focus on mastery of deep learning concepts, the application of interactive learning methods, and the use of educational technology. The training method was implemented continuously using a blended learning approach, including face-to-face sessions, practical workshops, mentoring, and the use of digital learning platforms. Evaluation results showed that 80% of training participants experienced significant improvements in their understanding of deep learning concepts, 70% were able to integrate interactive learning strategies into the teaching process, and 60% actively utilized learning technology to enrich students' learning experiences. These findings confirm that ongoing training integrated with technology support can improve teachers' capacity to implement deep learning in the classroom. Furthermore, the program's success is also influenced by intensive mentoring and collaboration among teachers through the Teacher Working Group (KKG). The implications of this research point to the need for educational policies at the elementary school level that encourage systematic, sustainable, and technology-based teacher professional development programs. Thus, the implementation of deep learning can be optimized to support the achievement of competency-based curriculum objectives and improve the overall quality of education